PP.40.08: NEUROVASCULAR DECOMPRESSION OF THE BRAIN STEM AND CATHETER-BASED RENAL DENERVATION OF RESISTANT HYPERTENSION IN THE SAME PATIENTS. (June 2015) - Fejes, I.; Bajcsi, D.; Nagy, F.T.; Ungi, I.; Voros, E.; Barzo, P.; Abraham, G.; Legrady, P.
Abstract : Objective: Nowadays there are more and more novel invasive methods in the therapy of high blood pressure. Here we present two cases with dual invasive sympatholytic therapeutic procedures of each one. Design and method: Patient 1 is a 60-year old man with obesity, impaired glucose tolerance, secondary hyperparathyeroidism, secondary hyperaldosteronism, severe obstructive sleep apnoe syndrome. Many of target organ damages are also known like left ventricular hypertrophy and hypertensive angiopathy. Patient 2 is a 37-year old woman with obesity, type-2 diabetes mellitus, left ventricular hypertrophy and hypertensive angiopathy. Results: In both cases neurovascular pulsatile compression (NVPC) of the rostral ventrolateral medulla on the left side were diagnosed. In 2010 successfull neurovascular decompresssions (NVD) were performed in both cases. But both patients' blood pressure (BP) started to increase again as did the number of antihypertensive agents too. In 2012 successfull catheter-based renal denervations (RDN) were performed in both cases. Mean BP of Patient 1 was 200/115 mm Hg with 12 different antihypertensive drugs before NVD. After it BP decreased to 165/100 mm Hg with only 5 different drugs. Mean BP of Patient 2 was 170/100 mm Hg with 10 drugs before NVD. After it her BP was 135/90 mm Hg with 4 drugs. Mean BP of Patient 1 was 214/123 mm Hg with 8 drugs 1 month prior to RDN, 155/100 mm Hg with 9 drugs at the time of RDN and 134/82 mm Hg with 5 drugs after 6 months of RDN. Mean BP of Patient 2 was 156/100 mm Hg with 10 drugs before RDN and 158/84 mm Hg with 6 drugs after 6 months later. Conclusions: NVD caused only a transient but significant decrease in BP as a simpatholytic procedure. Whether an RDN does only the same? Where is the real center of the sympathetic overactivity in hypertensives? Whether can we decrease the body sympathetic overactivity successfully permanently or do we always have to count for a newer and newer re-overactivation?